Plummer-Vinson syndrome: a case report - A. Bhat, Rafiq; Wani, Saleem A.; Soni, Pankaj (International Journal of Research in Medical Sciences, 2018)
Plummer-Vinson syndrome (PVS) also named as Patterson-Brown-Kelly syndrome is a combined presentation of three things- dysphagia, iron deficiency anemia, and esophageal webs, seen more often in middle aged females. A 30-year-old female presented to us with shortness of breath on exertion and long standing dysphagia and weight loss. After investigations she was found to be severely anemic. Upper GI endoscopy revealed esophageal web. Dilatation of esophageal web was done, anemia was corrected. Patient is on regular follow-up with marked improvement in terms of weight gain and increased functional capacity.